Hydrological modelling for a resilient future: innovations at the water-climate nexus - Sikka, Alok; Yadav, Shweta; Alam, Mohammad Faiz; Ghosh, Surajit; Bhatpuria, Dhyey; Padhee, Suman Kumar; Sahana, V.; Pandey, Shivam; Sena, Dipaka Ranjan (International Water Management Institute, 2025)
IWMI organized a side event at the XIIth IAHS Scientific Assembly 2025 on “Hydrological Modelling for a Resilient Future: Innovations at the Water–Climate Nexus” on 5 October 2025 at IIT Roorkee. The session showcased cutting-edge modelling tools, data-driven approaches, and interdisciplinary methods to tackle emerging water challenges under climate change. Researchers from IWMI, CGIAR Science Programs, and global partners presented innovations across the water–energy–food nexus, groundwater resilience, antimicrobial resistance (AMR), urban water quality, flood and drought forecasting, salinity prediction, and river basin digital twins.